Free abdominal fat transfer for partial and total parotidectomy defect reconstruction. (30th May 2016) - Loyo, Myriam; Gourin, Christine G.
Abstract : Objectives/Hypothesis: A variety of techniques have been proposed for reconstruction of the parotidectomy defect. We reviewed our experience with free abdominal fat transfer (FAT) graft reconstruction of parotidectomy defects for benign and malignant disease. Methods: The medical records of patients who underwent parotidectomy for benign or malignant disease from 2007 to 2015 were retrospectively reviewed. Results: One hundred and five patients underwent 108 parotidectomies with FAT reconstruction, with bilateral parotidectomy performed in three patients. The majority of patients had benign pathology (71%) and tumors < 3 cm (57%). Prior surgery had been performed in 13 cases (12%) and prior radiation had been performed in three (3%). Superficial parotidectomy was performed in 62 patients (57%) and concurrent elective neck dissection was performed in eight (7%). A facelift incision was utilized in 59 patients (55%). Postoperative radiation was used in 21 patients (19%). Abdominal donor site complications occurred in 11 patients (10%), consisting of hematoma in eight patients (7%) and seroma in three (3%). Parotidectomy wound dehiscence occurred in six cases (6%); all responded to conservative management. There was no association between age, tumor size, comorbidity, smoking status, extent of surgery, incision, or prior radiation on the development of wound complications. Fat transfer graft debulking was required in three patients with persistent overcorrection beyond 6 months postoperatively. No patient demonstrated undercorrection or further FAT resorption beyond 6 months. Conclusion: Fat transfer reconstruction of the parotidectomy defect is safe and achieves a consistent and predictable long‐term cosmetic result. Level of Evidence: 4. Laryngoscope, 126:2694–2698, 2016